Protein Binding of a Novel Platinum-Based Anticancer Agent BP-C1 Containing a Lignin-Derived Polymeric Ligand - Elena Fedoros (MDPI AG, 2021)
Platinum (Pt) antineoplastic agents remain indispensable for the treatment of oncological disease. Pt-based drugs are mainly used in the therapy of ovarian cancer and non-small-cell lung carcinoma. A novel platinum-containing antineoplastic agent BP-C1 is a complex of diamminoplatinum with an oxygen-donor polymeric ligand of benzene-polycarboxylic acids, isolated from natural lignin. The aim of the study was to investigate ex vivo protein binding of BP-C1. Protein binding of BP-C1 was tested using equilibrium dialysis. Pooled blood plasma was used in the study. Control solutions contained the same dosages of BP-C1 in PBS (pH 7.2). Plasma and control solutions were submitted to equilibrium dialysis across a vertical 8 kDa cut-off membrane for 4 h at 37 °C under gentle shaking. Platinum was quantified in dialysis and retained fractions using inductively coupled plasma mass spectrometry after microwave digestion. The dialysis system was tested and validated; this showed no protein saturation with platinum. A medium degree of binding of platinum to macromolecular species of ca. 60% was observed. The study showed the maintenance of a high fraction of free BP-C1 in the bloodstream, facilitating its pharmacological activity.